Gut lavage IgG and interleukin 1 receptor antagonist:interleukin 1 beta ratio as markers of intestinal inflammation in children with inflammatory bowel disease. Issue 1 (July 1997) - Troncone, R; Caputo, N; Campanozzi, A; Cucciardi, M; Esposito, V; Russo, R; De Vizia, B; Greco, L; Cucchiara, S
Abstract : BACKGROUND: Whole gut lavage is currently used as preparation before radiological or endoscopic examination of the large bowel. AIM: To validate the gut lavage technique for the assessment of mucosal inflammation, by measuring intestinal IgG and interleukin 1 beta (IL-1 beta) in the fluid obtained. PATIENTS: Sixteen children with Crohn's disease (CD), 14 with ulcerative colitis (UC), and 22 age matched controls. METHODS: Isotonic, non-absorbable polyethylene glycol based lavage solution was given orally or by nasogastric tube. Clear fluid was collected, filtered, and treated with protease inhibitors. IgG, IL-1 beta and IL-1-receptor antagonist (IL-1-ra) were measured by sandwich enzyme linked immunosorbent assay (ELISA). RESULTS: In patients with UC and CD, IgG and IL-1 beta levels were significantly (p < 0.001) higher than in controls. A positive correlation (p < 0.05) was found with disease activity scores. IL-1-ra levels were not significantly different in UC and CD, when compared with controls, but the IL-1-ra:IL-1 beta ratio was significantly (p < 0.01) lower in patients with UC and CD, and negatively (p < 0.001) correlated with IgG levels in lavage fluid. CONCLUSIONS: Gut lavage fluid IgG and IL-1 beta levels and IL-1-ra:IL-1 beta ratio may provide objective discrimination between active and inactive disease in children with inflammatory bowel disease.